2023
DOI: 10.1186/s12912-023-01261-5
|View full text |Cite
|
Sign up to set email alerts
|

How nurses’ job characteristics affect their self-assessed work environment in hospitals— Slovenian use of the practice environment scale of the nursing work index

Abstract: Background Nurses’ work environment influences nursing practice. Inappropriate working conditions are the result of underdeveloped workplace infrastructure, poor work organisation, inadequate education, and inappropriate staffing norms. The aim of this study was to describe and examine the predictors that affect nurses’ work environment using the Practice Environment Scale of the Nursing Work Index (PES-NWI). Methods The validation of the PES-NWI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In some European countries, like Slovenia, the postgraduate training of nurses is an incipient reality, a fact that impacts negatively on their job satisfaction. ( 24 In other countries, like Switzerland, more progress has been made in this line, positively impacting satisfaction. 25 In the United States, postgraduate training is widespread, which favors the nurses’ job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In some European countries, like Slovenia, the postgraduate training of nurses is an incipient reality, a fact that impacts negatively on their job satisfaction. ( 24 In other countries, like Switzerland, more progress has been made in this line, positively impacting satisfaction. 25 In the United States, postgraduate training is widespread, which favors the nurses’ job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The Slovenian RN4CAST study showed that professional development opportunities and educational opportunities are of crucial importance for respondents, which is a response to the hindrance of their professional development, followed by job satisfaction. Relationships with physicians and their behaviour toward nurses are also critical, as they influence nurses’ professional status, create their educational opportunities and promote the development of nursing as a profession and science ( 16 ).…”
Section: Discoursementioning
confidence: 99%
“…Creating an optimal working environment for nurses is an important task for managers and leaders, but also for national healthcare policy makers ( 16 ). Policymakers must make systemic changes that prioritise nurses’ well-being.…”
Section: Discoursementioning
confidence: 99%
See 2 more Smart Citations